2020
DOI: 10.1371/journal.pone.0242442
|View full text |Cite
|
Sign up to set email alerts
|

Variation in competition performance, number of races, and age: Long-term athlete development in elite female swimmers

Abstract: While talent development and the contributing factors to success are hardly discussed among the experts in the field, the aim of the study was to investigate annual variation in competition performance (AVCP), number of races per year, and age, as potential success factors for international swimming competitions. Data from 40’277 long-course races, performed by all individual female starters (n = 253) at the 2018 European Swimming Championships (2018EC) for all 10 years prior to these championships, were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…Therefore, master athletes seem to be able to maintain their physical performance with advancing age due to ultra-endurance sports [37]. Similar effects were shown at international swimming competitions, where the number of races per year and age proved to be a success factor [38].…”
Section: Older Athletes Get Faster In Last Decadesmentioning
confidence: 71%
“…Therefore, master athletes seem to be able to maintain their physical performance with advancing age due to ultra-endurance sports [37]. Similar effects were shown at international swimming competitions, where the number of races per year and age proved to be a success factor [38].…”
Section: Older Athletes Get Faster In Last Decadesmentioning
confidence: 71%
“…However, other work has shown that early pre-pubertal success (before age 12) was only weakly associated with success at the highest world-level [ 33 ]. Participation in numerous junior competitions and within-sport diversification in swimming are explanatory factors for achieving athletic excellence at the senior level [ 34 36 ]. It further appears that years of high-level competition have a positive impact in achieving better positions during the senior WC [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Block and 50 m split times were measured with an electronical timing system (Quantum Aquatics, Swiss Timing LTD, Corgémont, Switzerland). The 50 m swimming test with fins began with an official on-block competition start [ 21 ] and no limits to the length of the subsequent underwater phase [ 7 ]. At the 15 m and 25 m mark, cameras (CX550, Sony Group Corporation, Tokyo, Japan) collected 50 Hz video footages at a right angle to the swimming lane to determine 15 m and 25 m split times.…”
Section: Methodsmentioning
confidence: 99%